How to motivate the fifth generation? : balancing engagement and entitlement at Lee Kum Kee - Ward, John L., 1945- (SAGE Knowledge. Cases., 2017)
In mid-2013, the Lee family, which owned the Hong Kong based food and health product giant Lee Kum Kee (LKK), struggled with how best to increase involvement of the fifth generation (G5), the children of the company's current fourth-generation (G4) senior executives and governance leaders. Only two of the fourteen G5 members had joined the company, and few had expressed interest in further involvement, including in the multiple learning and development programs the business offered, such as a mentoring program. Many of the G5 cousins had expressed little interest in business careers in general, and none of them currently was serving as an LKK intern. G4 members observed that their children were busy with family obligations, hobbies, and emerging careers outside the business. G5's lack of interest in business and governance roles was part of a growing pattern of low family engagement in general, exhibited by the cancellation of recent family retreats (once an annual tradition) because of apathy and some underlying conflict. A history of splits among past generations of the Lee family regarding business leadership made the engagement issue even more meaningful and critical.Students will consider the challenge from the point of view of G4 family members David Lee, chairman of the family's Family Office, and his sister, Elizabeth Mok, who ran the Family Learning and Development Center. They and their three siblings saw engaging the next generation as a top priority, one related to key concepts including family-business continuity, generational engagement and empowerment, succession, emotional ownership, and intrinsic/extrinsic motivation.